PENGARUH KARAKTERISTIK INDIVIDU DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT CLADTEK BI METAL MANUFACTURING - Rahmat Hidayat; Anna Cavorina (Politeknik Negeri Batam, 2017)
This research aims to know about the influence of individual characteristics and work environment on employee performance, especially in the office of PT Cladtek BI-Metal Manufacturing. Respondents in this research are employees of this office section includes the HRD, Project, Purchasing, Finance, QA / QC, Logistics, Document Control, IT, Technical, Design and R & D. Researchers using multiple regression method in this research, the result of multiple regression method shows that there is partial influence on individual characteristic variables on employee performance of PT Cladtek Bi-Metal Manufacturing, the partial influence on work environment variables on employee performance PT Cladtek BI-Metal Manufacturing and the simultaneous influence on individual characteristic variable and work environment on employee performance of PT Cladtek BI-Metal Manufacturing.